Incidence and prevalence of inflammatory bowel disease in UK primary care: a population-based cohort study. Issue 7 (19th July 2020) - Pasvol, Thomas Joshua; Horsfall, Laura; Bloom, Stuart; Segal, Anthony Walter; Sabin, Caroline; Field, Nigel; Rait, Greta
Abstract : Objectives: We describe temporal trends in the recorded incidence of inflammatory bowel disease (IBD) in UK primary care patients between 2000 and 2018. Design: A cohort study. Setting: The IQVIA Medical Research data (IMRD) primary care database. Participants: All individuals registered with general practices contributing to IMRD during the period 01 January 2000–31 December 2018. Main outcome measures: The primary outcome was the recorded diagnosis of IBD. Results: 11 325 025 individuals were included and 65 700 IBD cases were identified, of which 22 560 were incident diagnoses made during the study period. Overall, there were 8077 incident cases of Crohn's disease (CD) and 12 369 incident cases of ulcerative colitis (UC). Crude incidence estimates of 'IBD overall', CD and UC were 28.6 (28.2 to 28.9), 10.2 (10.0 to 10.5) and 15.7 (15.4 to 15.9)/100 000 person years, respectively. No change in IBD incidence was observed for adults aged 17–40 years and children aged 0–9 years. However, for adults aged over 40 years, incidence fell from 37.8 (34.5 to 41.4) to 23.6 (21.3 to 26.0)/100 000 person years (average decrease 2.3% (1.9 to 2.7)/year (p<0.0001)). In adolescents aged 10–16 years, incidence rose from 13.1 (8.4 to 19.5) to 25.4 (19.5 to 32.4)/100 000 person years (average increase 3.0% (1.7 to 4.3)/year (p<0.0001)). Point prevalence estimates on 31 December 2018 for IBD overall, CD and UC were 725, 276 and 397 per 100 000 people, respectively. Conclusions: This is one of the largest studies ever undertaken to investigate trends in IBD epidemiology. Although we observed stable or falling incidence of IBD in adults, our results are consistent with some of the highest reported global incidence and prevalence rates for IBD, with a 94% rise in incidence in adolescents. Further investigation is required to understand the aetiological drivers.